Heterogeneity in cardiovascular death or hospitalization for heart failure benefits with flozins is linked to weight. (27th January 2023) - Ghosal, Samit; Sinha, Binayak; Mukherjee, Rik
Abstract: Aims: Cardiovascular outcome trials with sodium–glucose cotransporter 2 inhibitors (SGLT‐2is) have documented a positive impact on micro‐ and macrovascular complications of type 2 diabetes (T2D). Most analyses suggest that these benefits are independent of achieving metabolic control. This meta‐regression analysis was undertaken to explore the relationship between metabolic components positively influenced by SGLT‐2is and a reduction in cardiovascular death (CV death) or hospitalization due to heart failure (hHF). Methods and results: A database search was conducted using the Cochrane Library to identify relevant studies. Analysis was conducted using CMA and RStudio (2022.07.1) software. The hazard ratios of the individual studies were used to compute the random effects model mean effect size for CV death or hHF, and the prediction interval was used to identify the uncertainty in the summary treatment effect. Heterogeneity was quantified using Q statistics. A pooled population of 46 969 patients from five studies was included for analysis. The Cochrane risk of bias tool was used to assess the quality of the studies. There was a significant 23% reduction in CV deaths or hHFs in the SGLT‐2i arm compared with the placebo arm [hazard ratio (HR): 0.77, 95% confidence interval (CI) 0.70–0.85]. However, the prediction interval (0.57–1.05) and the Q statistics [8.06 > degrees of freedom ( df ) of 4] were indicative of uncertainty in the true effect or heterogeneity. Nearly 50% of the variance of the observed effects were related to the true effects ( I 2  = 50%). Among the moderators selected, a significant correlation of the outcomes was found with the weight variable ( P  < 0.01). Weight differential could explain the entire variance in true effect size ( R 2  = 1.00) ruling out any sampling error. Conclusions: The results of this meta‐regression analysis suggest that the beneficial effects of SGLT‐2is in reducing CV deaths and hHFs are related to the weight variable.